The Effect of Service Quality and Servicescape Towards Customer Satisfaction, Starbucks Coffee, Jakarta - Marie, Andhalia Liza (Jurnal Penelitian Pariwisata, 2019)
This study aims to determine the effect of Service Quality and Servicescape Towards Customer Satisfaction Starbukcs Coffee, Jakarta. This type of research is explanatory research with a quantitative approach and using survey methods conducted on 100 customers of Starbucks Coffee, Jakarta. Sampling using nonprobability sampling method with purposive sampling technique. Data processing is done by using multiple linear regression analysis tools. Based on hypothesis testing, the results of the t test show that servicescape and service quality have a significant simultaneous effect on customer satisfaction.